THE EFFECT OF CONCENTRATE SUBSTITUTION WITH FERMENTED LAMTORO LEAVES FLOUR (Leucaena glauca) IN RATION ON FEED CONSUMPTION, GROWTH AND FEED CONVERSION OF BROILER CHICKEN - D Widharto; L Risyani; R Almaratu (Bantara Journal of Animal Science, 2019)
This study was conducted to determine the effect of concentrate substitution with fermented lamtoro leaves flour (Leucaena glauca) in rations onfeed consumption, growth and feed conversion of broiler chicken. A total of 60 day-old broiler chickens were divided into 4 treatments and these treatments were : Control treatment (T-0), group of chickens that were given feed concentrated feed without any substitution; The Treatment Group 1 ( T-1 ) , group of chickens that were given concentrated feed that was partly replaced by Fermented Lamtoro leaves flour with 5% concentration;and Treatment group 2 (T-2), group of chickens that were given concentrated feed that was partly replaced by Fermented Lamtoro leaves flour with 10% concentration; and Treatment Group 3 (T-3), group of chickens that were given concentrated feed that was partly replaced by Fermented Lamtoro leaves flour with 15% concentration. Variables observed in this studywere: feed consumption, growth, and feed conversion of broiler chickens. The data that was obtained during the study from each treatment were :  1 ) feed consumptionwere 82,79 (T-0 ); 84,24 ( T-1 ); 84,01 ( T-2 ) and 82,36 gr / chicken/day (T-3), 2 ) and 42,89 ( T-0 ) , 45,92 ( T-1 ) , 46,13 ( T-2 ) , and 42,90 gr/ (T-3) chicken/day for growth, and 3 ) 1,94 ( t0 ); 1,84 ( t1 ); 1,82 ( t2 ); and 1,92 ( t-3 ) for feed conversion. Statistical tests indicates there is no significant difference on feed consumption, growth, and feed consumption.The conclusion of the study is that the substitution of feed concentrate with lamtoro (Leucaena glauca)  leaves flour fermentation does not affect feed consumption, growth, and feed conversion of broiler chickens